Spatial and seasonal variations of organic carbon-based nutrients in Setiu Wetland, Malaysia - Suhaimi Suratman; Nur Hayati Che Zan; Azyyati Abdul Aziz; Norhayati Mohd Tahir (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to assess spatial and seasonal variations of dissolved and particulate organic carbon (DOC and POC, respectively) in the Setiu Wetland, which is located in the southern region of the South China Sea coastal area. Surface water samples were collected monthly from October 2009-September 2010. In addition, the concentration of chlorophyll-a was determined. The DOC and POC mean concentration varied between 80-340 μM and 60-115 μM, respectively. The results showed that the concentrations of these parameters were mainly influenced by human activities and season. Higher concentrations of DOC (150-340 μM) and POC (75-115 μM) were found at stations near the populated area, aquaculture and palm oil plantation. In addition, higher concentrations of DOC (200-275 μM) and POC (105-150 μM) were also recorded during the monsoon season due to runoff from terrestrial sources and resuspension from bottom sediments. No significant correlation between the low molecular weight (LMW) fractions of DOC and chlorophyll-a (R2=0.0096, p>0.05) further supports the hypothesis that phytoplankton not playing key role in regulating the organic carbon distribution. Higher percentage of LMW DOC in monsoon season suggesting possible input of this fraction from land runoff to the wetland area.